Accrual-based earnings management and real activities manipulation to avoid losses: Evidence from unlisted public companies in Vietnam - Trần Thị Bích Duyên; Phạm Nguyễn Đình Tuấn (My University, 2020)
Accrual-based earnings management and real activities manipulation to avoid losses: Evidence from unlisted public companies in Vietnam
Keywords: Accrual-based EM; Real activities manipulation; Unlisted companies